2009
DOI: 10.4049/jimmunol.0801420
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin Ligase c-Cbl Down-Regulates FcγRIIa Activation in Human Neutrophils

Abstract: Little is known about the mechanisms that arrest FcγRIIa signaling in human neutrophils once engaged by immune complexes or opsonized pathogens. In our previous studies, we observed a loss of immunoreactivity of Abs directed against FcγRIIa following its cross-linking. In this study, we report on the mechanisms involved in this event. A stimulated internalization of FcγRIIa leading to the down-regulation of its surface expression was observed by flow cytometry and confocal microscopy. Immunoprecipitation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 82 publications
5
33
0
Order By: Relevance
“…We observed that both Fc␥Rs are required for an optimal phagocytosis of opsonized zymosan. They were similarly essential for the stimulation of tyrosine phosphorylation and degradation of Fc␥RIIa (29). Phagocytosis of IgG-opsonized zymosan by human neutrophils required an extracellular influx of calcium that was exclusively dependent on Fc␥RIIIb engagement.…”
Section: Recipient Of a Canadian Arthritis Network Graduate Award Andmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that both Fc␥Rs are required for an optimal phagocytosis of opsonized zymosan. They were similarly essential for the stimulation of tyrosine phosphorylation and degradation of Fc␥RIIa (29). Phagocytosis of IgG-opsonized zymosan by human neutrophils required an extracellular influx of calcium that was exclusively dependent on Fc␥RIIIb engagement.…”
Section: Recipient Of a Canadian Arthritis Network Graduate Award Andmentioning
confidence: 99%
“…Phagocytosis Assay-Alexa 488-conjugated zymosan A bioparticles were opsonized by incubation with 10 mg/ml human IgGs at 37°C for 1 h and washed twice in HBSS as described (29). A ratio of 10 particles/cell was added at 25 l of neutrophils (10 ϫ 10 6 cells/ml) preincubated as described in the corresponding legend to initiate phagocytosis.…”
Section: Methodsmentioning
confidence: 99%
“…Internalization of the chemoattractant receptors is transient and followed by a recycling to the plasma membrane while that of CD32a results in its proteasome-dependent degradation [48,49]. The mechanisms regulating receptor recycling differ from those involved in their internalization; for example, recycling, as opposed to internalization, of CXCL8 receptors is phosphorylation independent [50,53].…”
Section: Receptor Internalizationmentioning
confidence: 99%
“…Arrestins and dynamin also play a role in the internalization of CXCR1/2 which appears to be independent of the interaction with heterotrimeric G proteins as FPR internalization is not affected by pertussis toxin [54]. Engagement of the opsonin receptor CD32a similarly leads to its internalization and subsequent proteosomal degradation [49].…”
Section: Receptor Internalizationmentioning
confidence: 99%
See 1 more Smart Citation